2005
DOI: 10.1007/s10705-004-5286-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing groundwater levels caused by land-use changes on greenhouse gas fluxes from tropical peat lands

Abstract: Monthly measurements of carbon dioxide ͑CO 2 ͒, methane ͑CH 4 ͒ and nitrous oxide ͑N 2 O͒ fluxes in peat soils were carried out and compared with groundwater level over a year at four sites ͑drained forest, upland cassava, upland and lowland paddy fields͒ located in Jambi province, Indonesia. Fluxes from swamp forest soils were also measured once per year as the native state of this investigated area. Land-use change from drained forest to lowland paddy field significantly decreased the CO 2 ͑from 266 to 30 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 18 publications
11
98
2
3
Order By: Relevance
“…Methane fluxes measured here were several orders of magnitude lower than CO 2 fluxes and varied markedly among sites. The highest CH 4 fluxes from site 1 (R. taedigera) and site 5 (sawgrass swamp) are comparable to fluxes reported in the literature from Kalimantan(e.g., 0.35-2 mg CH 4 m -2 h 1 ; Furukawa et al 2005;Hadi et al 2005;Jauhiainen et al 2005), while the lowest CH 4 fluxes at the three intermediate sites in the current study (C. panamensis and mixed forest) are comparable to those reported for Sarawak wetlands (maximum rates of 11.2 lg CO 2 m -2 h -1 ; Melling et al 2005a, b). Our results suggest that CH 4 fluxes have high spatial variability in peatland systems and vary in response to differences in the water table Hadi et al 2005;Jauhiainen et al 2005) and substrate availability (Bachoon and Jones 1992) to a greater extent than CO 2 fluxes.…”
Section: Discussionsupporting
confidence: 77%
“…Methane fluxes measured here were several orders of magnitude lower than CO 2 fluxes and varied markedly among sites. The highest CH 4 fluxes from site 1 (R. taedigera) and site 5 (sawgrass swamp) are comparable to fluxes reported in the literature from Kalimantan(e.g., 0.35-2 mg CH 4 m -2 h 1 ; Furukawa et al 2005;Hadi et al 2005;Jauhiainen et al 2005), while the lowest CH 4 fluxes at the three intermediate sites in the current study (C. panamensis and mixed forest) are comparable to those reported for Sarawak wetlands (maximum rates of 11.2 lg CO 2 m -2 h -1 ; Melling et al 2005a, b). Our results suggest that CH 4 fluxes have high spatial variability in peatland systems and vary in response to differences in the water table Hadi et al 2005;Jauhiainen et al 2005) and substrate availability (Bachoon and Jones 1992) to a greater extent than CO 2 fluxes.…”
Section: Discussionsupporting
confidence: 77%
“…In general, the results of CH 4 emission reduction followed by methane consumption fully agree with those of other studies that evaluated the effect of lowering the water-table level by draining in flooded soils in several parts of the world Nykanen et al, 1995;Maljanen et al, 2004;von Arnold et al, 2005;Furukawa et al, 2005;Bridgham et al, 2006;Elder & Lal, 2008;Jauhiainen et al, 2008;Jiang et al, 2009;Huang et al, 2010;Page & Dalal, 2011). All these authors showed that small water-table decreases cause drastic reductions in methane emissions, demonstrating the strong effect of drainage on CH 4 fluxes.…”
Section: In Drained Histosolssupporting
confidence: 87%
“…Some studies report positive effects of both temperature and pluvial precipitation (Jiang et al, 2009), others only of precipitation but not of temperature (Inubushi et al, 2003;Furukawa et al, 2005) In paddy rice fields, emissions reached 489 kg ha -1 yr -1 CH 4 in a Histosol in Indonesia and 586 kg ha -1 yr -1 CH 4 in a Planosol (Sousa, 2013) and 623 kg ha -1 yr -1 CH 4 in a Gleysol, the latter two in Rio Grande do Sul, Brazil (Zschornack, 2011). These values indicate that methane emission is much higher from paddy rice soils than from the natural Histosol in this study.…”
Section: Results and Discussion Ch 4 Fluxes In Natural Histosolmentioning
confidence: 99%
See 2 more Smart Citations